Weighted cross-validation evolving artificial neural networks to forecast time series - Peralta Donate, Juan (2011)
Accurate time series forecasting is a key tool to support decision making and for planning our day to-day activities. In recent years, several Works in the literature have adopted evolving artiﬁcial neural networks (EANN) for forecasting applications. EANNs are particularly appealing due to their ability to model an unspeciﬁed non-linear relationship between time series variables. In this Work, a novel approach for EANN forecasting systems is proposed, where a weighted cross-validation is used to build an ensemble of neural networks. Several experiments Were held, using a set of six real-world time series (from different domains) and comparing both the weighted and standard cross-validation variants. Overall, the weighted cross-validation provided the best forecasting results.